Respuesta agronómica del cultivo de papa (Solanum tuberosum L.) variedad chaucha a la aplicación de ácidos húmicos. - Herrera Gallo, Kevin Xavier (2022)
The objective of this study was to evaluate the agronomic response of potato (Solanum tuberosum L.) variety chaucha, under the influence of humic acids under open field conditions in the El Deseo sector of the Pangua canton (Cotopaxi, Ecuador). The established experimental design was completely randomized blocks (DBCA), with five treatments and four repetitions, which included chemical synthesis fertilization at 100% NPK according to the needs of the crop. The variables evaluated were: plant height (cm), stem diameter (cm), number of stems, number of tubers per plant, tuber weight per plant (g), tuber diameter (cm) and yield. of the crop. For the statistical analysis, the Infostat 2018 program was used and for the comparison of the measurements, the Tukey test p < 0.05 was used. The analysis of results showed that treatment one T1 (NPK 100% + A.H.E 100%) presentéd the highest yield with 11.10 t/ha. It is shown that the combination of humic acids plus chemical fertilization is a viable alternative to complement and increase efficiency in potato cultivation, it helps to stimulate better plant growth and the use of minerals, which makes it a sustainable option. to improve the biological properties of the soil.